Pathways Regulating Cytosolic Phospholipase A(2) Activation and Eicosanoid Production in Macrophages by Candida albicans - Suram, Saritha (American Society for Biochemistry and Molecular Biology, 2010)
Resident tissue macrophages are activated by the fungal pathogen Candida albicans to release eicosanoids, which are important modulators of inflammation and immune responses. Our objective was to identify the macrophage receptors engaged by C. albicans that mediate activation of group IVA cytosolic phospholipase A(2) (cPLA(2)α), a regulatory enzyme that releases arachidonic acid (AA) for production of prostaglandins and leukotrienes. A comparison of peritoneal macrophages from wild type and knock-out mice demonstrates that the β-glucan receptor Dectin-1 and MyD88 regulate early release of AA and eicosanoids in response to C. albicans. However, cyclooxygenase 2 (COX2) expression and later phase eicosanoid production are defective in MyD88(−/−) but not Dectin-1(−/−) macrophages. Furthermore, C. albicans-stimulated activation of MAPK and phosphorylation of cPLA(2)α on Ser-505 are regulated by MyD88 and not Dectin-1. In contrast, Dectin-1 mediates MAPK activation, cPLA(2)α phosphorylation, and COX2 expression in response to particulate β-glucan suggesting that other receptors engaged by C. albicans preferentially mediate these responses. Results also implicate the mannan-binding receptor Dectin-2 in regulating cPLA(2)α. C. albicans-stimulated MAPK activation and AA release are blocked by d-mannose and Dectin-2-specific antibody, and overexpression of Dectin-2 in RAW264.7 macrophages enhances C. albicans-stimulated MAPK activation, AA release, and COX2 expression. In addition, calcium mobilization is enhanced in RAW264.7 macrophages overexpressing Dectin-1 or -2. The results demonstrate that C. albicans engages both β-glucan and mannan-binding receptors on macrophages that act with MyD88 to regulate the activation of cPLA(2)α and eicosanoid production.